Kearifan Lokal Hajat Laut Budaya Maritim Pangandaran - Heriyawati, Yanti; Herdiani, Een; Dimyati, Ipit Saefidier (LP2M ISBI Bandung, 2020)
ABSTRACTHajat Laut (sea celebration) as a tradition of Pangandaran coastal community has been changing as thechanging of the people’s social structure. Pangandaran, a regency which is famous of sea tourism object,still maintains the ritual of Hajat Laut containing local wisdom. This writing is aimed at analyzinghow Hajat Laut as a primordial cultural heritage of nautical community adapts with the social economydevelopment of the people. Mircea Eliade’s view is applied to trace the old views containing local wisdom.Meanwhile, Thomas Kuhn’s proposition bridges the discussion on paradigm dynamics toward theevents of Hajat Laut. in addition to literature study, the data are obtained through observation basedon characteristics of qualitative research. The result shows that Hajat Laut as the heritage of primordialsociety passes through an interpretation process from each of the generations. The anomaly existingin the process of paradigm debates place Hajat Laut in the presence and position adjusting to the livedevelopment need of Pangandaran society as a tourism city. At the same time, the economic, social, andreligious needs are fulfilled by keep maintaining the local wisdom of the culture.Keywords: local wisdom, hajat laut, coastal, PangandaranABSTRAKHajat Laut sebagai tradisi masyarakat pesisir Pangandaran telah mengalami perubahandengan perubahan struktur sosial masyarakatnya. Pangandaran sebagai kabupaten yangterkenal dengan objek wisata laut ini masih menyimpan ritual Hajat Laut yang bermuatankearifan lokal. Tulisan ini bertujuan mengkaji bagaimana Hajat Laut sebagai warisan budayaprimordial masyarakat laut mengalami proses adaptasi dengan perkembangan sosial ekonomimasyarakatnya. Pemikiran Mircea Eliade digunakan untuk menelusuri jejak-jejak pemikiranlama yang bermuatan kearifan lokal. Sementara pandangan Thomas Kuhn menjembatani dalampembahasan dinamika paradigma terhadap peristiwa Hajat Laut. Selain studi pustaka, datadatapenelitian dikumpulkan melalui observasi berdasarkan karakteristik penelitian kualitatif.Hasil kajian menunjukkan bahwa, Hajat Laut sebagai warisan masyarakat primordial melewatiproses interpretasi dari setiap generasinya. Anomali yang terjadi dalam proses perdebatanparadigma menempatkan Hajat Laut kini hadir dan mengalir sesuai dengan perkembangankebutuhan hidup masyarakat Pangandaran, sebagai kota wisata. Secara bersamaan pemenuhankebutuhan ekonomi, sosial, dan religi terpenuhi dengan tetap mempertahankan nilai-nilaikearifan lokal budayanya.Kata Kunci: kearifan lokal, hajat laut, pesisir, Pangandaran